2017
DOI: 10.1556/066.2017.46.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying and process optimization of sour orange juice

Abstract: In this study, production of sour orange juice powder utilizing a spray dryer was investigated. To prevent stickiness, maltodextrin DE 12 was used as a drying agent. While feed fl ow rate, feed temperature, and air fl ow rate were kept constant, inlet air temperature (120-160 °C) and maltodextrin content (maltodextrin dry solids/100 g feed mixture dry solids; 10-20%, w/w) were selected as the independent variables. Product properties investigated included ascorbic acid, volatile compounds, and moisture content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
4
2
0
Order By: Relevance
“…On the other hand, at high inlet air temperature, the extreme water loss caused the cracking of the particle membrane and induced a subsequent premature degradation of the encapsulated vitamin by the contact with air. This effect is in accordance with those reported in previous studies (Cuevas‐Glory et al, ; Pino et al, ). The temperature of the air cannot be so high that it causes thermal damage.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…On the other hand, at high inlet air temperature, the extreme water loss caused the cracking of the particle membrane and induced a subsequent premature degradation of the encapsulated vitamin by the contact with air. This effect is in accordance with those reported in previous studies (Cuevas‐Glory et al, ; Pino et al, ). The temperature of the air cannot be so high that it causes thermal damage.…”
Section: Resultssupporting
confidence: 94%
“…Table showed that the ascorbic acid retention ranges from 73.3 to 89.9%, representing that the difference between the maximum and minimum value of ascorbic acid retention was 16.6%, which is due to the high sensitivity of this vitamin to high temperatures. These results were close to the 79.5% found for the spray drying of guava pulp (Chopda & Barrett, ) and 66.7–80.5% (Patil et al, ), as well as of other fruit juices dried by the same technique (Islam et al, ; Cuevas‐Glory et al, ; Pino et al, ).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, the inlet air temperature is usually determined by the temperature, which can safely be used without damaging the product (GHARSALLAOUI et al, 2007). The pattern of the fi ndings was similar to those found for other fruit juices (PATIL et al, 2014;CUEVAS-GLORY et al, 2017). Nevertheless, other studies reported an opposite effect (MOREIRA et al, 2010;SINGH et al, 2013), but in all cases higher inlet air temperatures were used.…”
Section: Resultssupporting
confidence: 66%